PERAN WANITA NELAYAN DALAM PENGEMBANGAN INDUSTRI KRUPUK IKAN: PEMBERDAYAAN UNTUK PENINGKATAN PRODUKSI DI KELURAHAN SERANGAN - Farhaeni, Mutria; Martini, Luh Kadek Budi; Lestari, Putu Astri (Jurnal Abdi Insani, 2024)
Fish cracker UMKM is an inseparable part of the fishermen's family, has an important role in the family economy. Increasing the role of women through the development of productive economic businesses is one of the efforts to empower women in utilizing fishery resources, which has implications for increasing the income of fishermen's households. With the involvement of women in supporting the family economy, difficulties in meeting the needs of life can be reduced. This community service activity aims to improve knowledge and skills in processing fish cracker products. Community service activities were carried out in Serangan Village, South Denpasar District. The total number of participants who attended this activity was 7 (seven) people. The method used to solve the problem was to conduct socialization activities, training and mentoring of fish crackers as well as packaging, product labeling and content creation. The results achieved were an increase in knowledge, understanding and skills of participants in the field of fish skin cracker production process and packaging, attractive labeling and content creation on Instagram social media. Partners stated that this activity was in accordance with the needs of partners, namely being able to empower the community, especially fish skin cracker business owners in Serangan Village.